Castelman’s disease – case report and review of the literature - Lewandowska, Aleksandra; Ziółkowska, Ewa; Grzela, Monika; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2003)
Castelman’s disease is also known as angiofollicular lymphoid hyperplasia or giant lymph node hyperplasia, lymph nodal hamartoma and benign giant lymphoma. It was first described in 1956, in a group of patients with localized mediastinal lymph node enlargement. It is currently classified into two major subgroups: localized Castelman’s disease and multicentric (disseminated) Castelman’s disease. There are three histologic variants: hyaline-vascular, plasma cell and transitional (mixed type). The underlying cause of Castelman’s disease is unknown, however several theories have been formulated to account for the spectrum of associated pathologic and clinical features. Several neoplastic, autoimmune, infectious diseases can mimic Castelman’s disease. Although histologic features in this disease are characteristic, they are not specific. „Castelman’s disease-like” changes have been reported in a wide range of conditions. Similar histologic changes reported in lymph nodes in patients with Hodgkin’s disease have led to diagnostic errors. A close communication between the clinician and the pathologist is essential to arrive at the correct diagnosis. Hyaline-vascular Castelman’s disease is considered benign and self-limited, with a 5-year survival approaching 100%. Surgical resection is the primary treatment of this variant and is curative in virtually all cases. Disseminated or multicentric Castelman’s disease is currently regarded as a potentially malignant lymphoproliferative disorder associated with POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal proteinemia and skin changes) syndrome, osteosclerotic myeloma, Kaposi sarcoma and AIDS. This variant of Castelman’s disease is associated with a poor outcome. The overall mortality rate is about 50% with a median survival of 26 months. In this variant, the treatment with a combination of radiation therapy, corticosteroids and chemotherapy is recommended. Several immunosuppressive agents (cyclophosphamide, azathioprine) have been used in the treatment of multicentric disease with anecdotal reports of efficacy. The optimal therapeutic regimen for Castelman’s disease is unknown.